2007
DOI: 10.1128/jvi.01899-06
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic, Compensatory Mutational Events in the Capsid of Foot-and-Mouth Disease Virus in Response to the Introduction of Mutations Found in Viruses from Persistent Infections

Abstract: The evolution of foot-and-mouth disease virus (FMDV) (biological clone C-S8c1) in persistently infected cells led to the emergence of a variant (R100) that displayed increased virulence, reduced stability, and other modified phenotypic traits. Some mutations fixed in the R100 genome involved a cluster of highly conserved residues around the capsid pores that participate in interactions with each other and/or between capsid protomers. We have investigated phenotypic and genotypic changes that occurred when thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…A large number of mutations in tightly organized RNA viral genomes should lead to frequent epistatic interactions between sites. Several experiments have provided strong evidence of extensive epistasis in RNA viruses, confirming that during viral evolution certain substitutions at different sites may occur in a coordinated manner (7)(8)(9)(10)(11)(12). Experimental studies into the adaptation of genetically modified HCV genomes propagated in cell culture also have shown antagonistic epistatic interactions between deleterious mutations exhibited in the form of compensatory mutations (13)(14)(15).…”
mentioning
confidence: 99%
“…A large number of mutations in tightly organized RNA viral genomes should lead to frequent epistatic interactions between sites. Several experiments have provided strong evidence of extensive epistasis in RNA viruses, confirming that during viral evolution certain substitutions at different sites may occur in a coordinated manner (7)(8)(9)(10)(11)(12). Experimental studies into the adaptation of genetically modified HCV genomes propagated in cell culture also have shown antagonistic epistatic interactions between deleterious mutations exhibited in the form of compensatory mutations (13)(14)(15).…”
mentioning
confidence: 99%
“…1. Spatially close compensatory mutations were also observed in the foot-and-mouth disease virus capsid and in the DNA bacteriophage ÎŚX174 (Mateo and Mateu, 2007;Poon and Chao, 2005). Analysis of compensatory mutation frequency in DNA bacteriophage ÎŚX174 revealed that many compensatory mutations occur at spatially close residues (Poon and Chao, 2005).…”
Section: A B a B A Bmentioning
confidence: 94%
“…Therefore, it is unlikely that soluble scFv2 is directed to internally located residues and T4→S was discarded as a possible antigenic site. The T4→S residue change could be accounted for either as a result of a compensatory mutational event due to possible structural rearrangements following a distant effect (Grazioli et al, 2006;Mateo and Mateu, 2007) or due to the quasispecies nature of FMDV. Since the majority of virus escape mutants involve the interaction of a surfaceorientated side-chain with a MAb, the surface exposed residue change R159→H in VP1, located at the C-terminal base of the G-H loop, was thought to be involved in binding of the soluble scFv2.…”
Section: Discussionmentioning
confidence: 99%